The Realization of Ideology of Translation in Rendering Figurative Language in Dashner’s The Fever Code - Ilyas, Muhammad; Sutopo, Djoko; Mujiyanto, Januarius (English Education Journal, 2019)
Translation involves at least two languages which come from the source language (SL) and target language (TL). In addition, it also involves the ideology in all of the translation fileds including novel. Novel has many components on it including figurative language. It means that the ideology depends on the belief of the writer or the translator which deals with two domain; foreignization and domestication. The realization of ideology of figurative language translation needs to be investigated to find out the translator's tendency. This study is a descriptive qualitative study. The main objective of the study is to explain the realization of ideology in rendering figurative language from English into Indonesian in Dashner’s The Fever Code. In order to collect the data, the researchers used the document. The document was used to collect of figurative language from both English and its Indonesian translation including simile, metaphor, personification, hyperbole, and irony. Then, they were analyzed the translation method used by the translator and the realization of ideology in rendering figurative language. The finding shows that two translation tendencies involves in translating process; they are SL emphasizes and TL emphasizes. The SL emphasizes involves literal translation, faithful translation, and semantic translation. Meanwhile, TL emphasizes involves free translation, idiomatic translation, and communicative translation. The SL emphasizes matches the foreignization which introduces what is foreign and unknown to the target readers, taking the reader cover to the foreign culture and making the target readers see the cultural and linguistic differences; it also enables the better understanding and appreciation of the thoughts and lives of foreign people. Moreover, TL emphasizes matches domestication which brings what foreign and unknown the cultural and linguistic differences to the target readers. The findings can be concluded that the employing translation method leads to the translator to realize the ideology in rendering figurative language; simile, metaphor, personification, hyperbole, and irony.